Implications of the ammonia distribution on Jupiter from 1 to 100 bars as measured by the Juno microwave radiometer. Issue 15 (5th August 2017) - Ingersoll, Andrew P.; Adumitroaie, Virgil; Allison, Michael D.; Atreya, Sushil; Bellotti, Amadeo A.; Bolton, Scott J.; Brown, Shannon T.; Gulkis, Samuel; Janssen, Michael A.; Levin, Steven M.; Li, Cheng; Li, Liming; et al.
Abstract: The latitude‐altitude map of ammonia mixing ratio shows an ammonia‐rich zone at 0–5°N, with mixing ratios of 320–340 ppm, extending from 40–60 bars up to the ammonia cloud base at 0.7 bars. Ammonia‐poor air occupies a belt from 5–20°N. We argue that downdrafts as well as updrafts are needed in the 0–5°N zone to balance the upward ammonia flux. Outside the 0–20°N region, the belt‐zone signature is weaker. At latitudes out to ±40°, there is an ammonia‐rich layer from cloud base down to 2 bars that we argue is caused by falling precipitation. Below, there is an ammonia‐poor layer with a minimum at 6 bars. Unanswered questions include how the ammonia‐poor layer is maintained, why the belt‐zone structure is barely evident in the ammonia distribution outside 0–20°N, and how the internal heat is transported through the ammonia‐poor layer to the ammonia cloud base. Key Points: The altitude‐latitude map of Jupiter's ammonia reveals unexpected evidence of large‐scale circulation down at least to the 50‐bar level A narrow equatorial band is the only region where ammonia‐rich air from below the 50‐bar level can reach the ammonia cloud at 0.7 bars At higher latitudes the ammonia‐rich air appears to be blocked by a layer of ammonia‐poor air between 3 and 15 bars Plain Language Summary: Jupiter is a fluid planet. It has no solid continents to stabilize the weather. Scientists have wondered what the weather is like below the clouds because it might explain why storms last for decades or hundreds of years on Jupiter. The Juno spacecraft is the first chance we have had to take a look beneath the clouds, and this is the first analysis of the Juno data. The surprise is that, deep down, Jupiter's weather looks a lot like Earth's, with ammonia gas taking the place of water vapor. There is a band of high humidity at the equator and bands of low humidity on either side of the equator, like Earth's tropical and subtropical bands. What is different is that the bands go much deeper than anyone expected and this is all taking place on a planet without an ocean or a solid surface.